The Synthesis of Cinchonine Tiglat Ester Compound and Cytotoxic Test Against MCF-7 Breast Cancer Cell - Ahmad Khanifudin; Gian Primahana; Sylvia Rizky Prima; Puspa Dewi Lotulung; Muhammad Hanafi (Jurnal Kimia Terapan Indonesia, 2017)
Cinchonine is a type of cinchona alkaloid compound commonly found and/or isolated from Cinchona sp. plant. It is commonly used to treat malaria, and can potentially be used against cancer cells. In this particular study, cinchonine ester derivatives were extracted through esterification processs. Synthesized esther is aimed to gain higher lipophilicity of cinchonine so that makes it easier to pass through cell membrane. Esterification was done using DCC activator as well as DMAP catalyst with tiglic acid used to create cinchonine tiglat. Subsequent cinchonine tiglat was obtained in the form of oil with 25,28% yield. The compound obtained from the synthesis was the analyzed using LC-ESI-MS and 1H-NMR spectroscopy instrumentation. Results show that the target compound has been successfully synthesized. Its cytotoxic ability against MCF-7 breast cancer cells was tested using the Alamar Blue method. Results concluded that cinchonine tiglat ester compound has a viable cytotoxic activity with IC50 value of 1.22 ppm.